Evidence of confusion about evidence of causes: comments on the debate about EBP in education. Issue 1 (17th February 2019) - Phillips, D. C.
ABSTRACT: EBP – evidence-based policy and practice – has generated intense controversy. A rough continuum of positions can be discerned: At one pole are "tough-minded" commentators distinguished by their support of EBP; however, there are serious internal differences in this camp, for some regard randomised field trials (RFTs) as the gold standard methodology that should generate the evidence required in EBP; while other "softer" commentators have a more nuanced position wherein the RFT is an INUS factor – part of a "causal cake" which requires many other support factors to be present before any generalisation can be made about a policy. The evolution of this softer branch of the tough-minded pole is traced, from Campbell and Stanley, to Cronbach and Associates, to Cartwright and Hardie. At the other pole are the tender-minded, many of whom are members of the philosophy of education community; they are sceptical about EBP, perhaps the most serious of their criticisms being that educational processes are not apt for causal investigation at all. The arguments that are offered in support of this position are judged to be deficient.